A hybrid method of detecting flame from video stream. Issue 11 (16th May 2022) - Dou, Zengfa; Ma, Xiaoke; Xie, Xianghua; Liu, Hui; Guo, Chubing
Abstract: In this paper, a method of detecting flame from video stream is proposed exploiting the characteristics of the disordered movement, rapid deformation and intense colour of the flame. Firstly, the frame difference between video frame and background frame is calculated to obtain the main part of the moving object, and the difference between frames is calculated frame by frame in time series to obtain the deformation part of the moving object, and then the sum of cumulative difference between frames and the background difference between frames are added to generate a binary image containing the moving object and the deformed part. Secondly, the binary image is morphologically opened, and rectangular segmentation is carried out to obtain multiple suspicious flame regions. Finally, in the light of the intense colour of the flame, the corresponding area is extracted from the original picture by using the segmentation rectangle, and the colour statistics of the area are carried out to further judge whether there is a burning flame in the area. The experimental results show that the algorithm can accurately detect the burning area of flame in the real scene and eliminate the light interference and the movement interference.